Karakteristik Mazmur Rajani - Darto Sachius (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2022)
This study is entitled Characteristic of Psalm Rajani. This research will look for the characteristics of the Royal Psalms in the Book of Psalms. The research method used is qualitative not experimental. With the following steps, first by analyzing the passage according to its elements, second by knowing the style of poetry in Hebrew poetry, third trying to express the beauty of the language of poetry well, fourth trying to explain the meaning of Hebrew verse. So it is hoped that with this method can be formulated the characteristics of the Royal Psalms. So the three important things in the Royal Psalm are, firstly this psalm reflects the unique relationship between God and the king, secondly the holy king is the mediator of Divine blessing. All three charismatic kings ruled by divine gift. Even the kings of Israel received their dominion with God's approval like a royal coronation.